Arteriovenous shunt graft ulceration with sinus and graft epithelialization - Pooja Singhal; Adriana Luk; Amar Ibrahim; Minhui Laura Kim; Jagdish Butany (Elsevier, 2015)
Arteriovenous fistula and grafts are used as access sites for patients with chronic kidney disease and are prone for complications. Stent grafts are used to treat access site complications. We report a rare and unusual finding of epithelialization of the sinus tract and the lumen of a polytetrafluoroethylene graft, following ulceration of the overlying skin.